THE EFFECT OF SELF-EFFICACY ON ENGLISH TRAINING RESULTS - Bayu Adi Laksono (IKIP Siliwangi Bandung, 2018)
The aim of this study is to explore how much influence the self-efficacy of English training results in the form of the TOEFL score. This research used the quantitative approach, with multiple linear regression analysis. The sampling technique used a saturated sample in which the researcher uses 23 persons who are carrying out the TOEFL training. Data collection techniques using the questionnaire in the form of google form and then analyzed using SPSS 24. Data collection tool in the form of the validated questionnaire with all item coefficients greater than 0.3 (r = 0.316 — 0.885) and declared reliable with alpha value 0.945. The results of this study indicate that there is a significant influence simultaneously between self-efficacy with ability variables, the ability to organize, the ability to perform a task, the ability to achieve a goal and implement actions to achieve proficiency in training results in the form of TOEFL score. But partially no significant effect. Effect of self-efficacy with these variables has an effect on the training results in the form of TOEFL score of 64.5%.